Learning in the time of COVID-19: capitalizing on the opportunity presented by the pandemic - Trombly, Christopher E. (Journal of Professional Capital and Community, 2020)
Purpose: This paper addresses the current disruption in the educational status quo ante that has been caused by the worldwide outbreak of COVID-19. Its purpose is to suggest how practicing educators, their professional associations and the university-based researchers with whom they partner might capitalize on the unanticipated opportunity to impact education policy that the pandemic presents. Design/methodology/approach: The author draws upon his own preparation and experiences – first as a long-time practitioner in the elementary and secondary school setting, then as a university professor – to offer insights and suggestions to practicing educators, their professional associations and the university-based researchers with whom they partner. Findings: Despite the unexpected challenges that the COVID-19 pandemic has presented to educators – challenges to which educators around the globe have risen admirably – the current crisis also affords practicing educators, their professional associations and the university-based researchers with whom they partner to change the status quo ante for the better. Originality/value: The particular value of this piece is twofold: its analysis of the impact of this unanticipated crisis upon education by an author who has served both in the elementary/secondary setting and at the university level, and its assertion that educators must avail themselves of this once-in-a-lifetime opportunity to change the educational status quo ante for the better. © 2020, Emerald Publishing Limited.
17 citations (Crossref) [2023-10-31] WOS:000546450400001
Keywords: Collaboration; Community; Professional judgment; dept.edl; peer-reviewed

Impact of supervision and evaluation on the professional development of school-based speech-language pathologists - Brown, Jacqueline; Trombly, Christopher; Roitsch, Jane (Perspectives of the ASHA Special Interest Groups, 2025)
Keywords: American Speech-Language-Hearing Association; Asha; Developmental psychology; Language development; Linguistics; Medical education; Medicine; Pedagogy; Professional development; Psychology; dept.edl

School Leadership for Learning: Learning Theory to Improve Professional Practice - Gregory, Jess L.; Ben-Avie, Michael; Billups, Felice; Grassetti, Mary; Hesser, Tiffany; Lawlor, Jennifer Lynne; Martone, Drey; Maykel, Cheryl; Minkos, Marlena L.; Paslov, Linda; Trombly, Christopher; Tucker, Lauren; et al. (Jess L. Gregory, 2021)
Keywords: Educational leadership; School administrators; Handbooks; manuals; etc; In-service training; School administrators; In-service training; Teachers; dept.edl; dept.sed; faculty_collection